2019
DOI: 10.1371/journal.pbio.2006806
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions modify the temperature dependence of community biomass and ecosystem function

Abstract: Aquatic ecosystems worldwide continue to experience unprecedented warming and ecological change. Warming increases metabolic rates of animals, plants, and microbes, accelerating their use of energy and materials, their population growth, and interaction rates. At a much larger biological scale, warming accelerates ecosystem-level processes, elevating fluxes of carbon and oxygen between biota and the atmosphere. Although these general effects of temperature at finer and broader biological scales are widely obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…Fish in small mountain streams also have limited opportunities for habitat tracking and dispersal (Herrera‐R et al ., 2020 ; Taniwaki et al ., 2017 ). Recent studies from other areas suggest a range of potential impacts including changes in the distribution of species and trophic assemblages (Garzke et al ., 2019 ; Herrera‐R et al ., 2020 ), the age of sexual maturity (Shahjahan et al ., 2017 ), metabolic rates (Petitjean et al ., 2019 ), nutrient composition (Colombo et al ., 2019 ), contaminant absorption (Schartup et al ., 2019 ) and alterations in sex ratios (Fernandino & Hattori, 2019 ). Rarer cold water species at high elevations are likely to be impacted the most (Buisson et al ., 2008 ; Herrera‐R et al ., 2020 ), suggesting that high‐elevation Astroblepus spp.…”
Section: The Factors Causing the Decline Of Ecuador's Freshwater Fishesmentioning
confidence: 99%
“…Fish in small mountain streams also have limited opportunities for habitat tracking and dispersal (Herrera‐R et al ., 2020 ; Taniwaki et al ., 2017 ). Recent studies from other areas suggest a range of potential impacts including changes in the distribution of species and trophic assemblages (Garzke et al ., 2019 ; Herrera‐R et al ., 2020 ), the age of sexual maturity (Shahjahan et al ., 2017 ), metabolic rates (Petitjean et al ., 2019 ), nutrient composition (Colombo et al ., 2019 ), contaminant absorption (Schartup et al ., 2019 ) and alterations in sex ratios (Fernandino & Hattori, 2019 ). Rarer cold water species at high elevations are likely to be impacted the most (Buisson et al ., 2008 ; Herrera‐R et al ., 2020 ), suggesting that high‐elevation Astroblepus spp.…”
Section: The Factors Causing the Decline Of Ecuador's Freshwater Fishesmentioning
confidence: 99%
“…Food webs describe species interactions within and between various trophic levels, and their composition dictates biodiversity-ecosystem functionality 30 , 31 . As a key food web metric, network generality (i.e., mean number of host or prey species per consumer) mediates ESs 32 , with high generality entailing the presence of multiple prey or host items for each consumer (i.e., predator or parasitoid) within the food web 33 , 34 and thereby mitigating impacts of eventual species loss 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous experimental studies have reported that warming can promote changes toward smaller cells when nutrient stress intensifies (Peter and Sommer, 2013), increase carbon:nitrogen (C:N) ratios (Biermann et al, 2015), primary productivity and biodiversity (Yvon-Durocher et al, 2015), and reduce the efficiency of energy transfer from primary producers to herbivores and detritivores (Ullah et al, 2018). Also, warming can strengthen the predator-consumer interaction (Schaum et al, 2018b;Garzke et al, 2019), and ultimately weaken the C-sink capacity, as shown in experimental microbial plankton communities (Yvon-Durocher et al, 2017). Surprisingly, it is still poorly understood how the interaction between warming and temperature fluctuation affects the composition, dynamics and metabolism of microbial food webs.…”
Section: Introductionmentioning
confidence: 99%